Adsorption Equilibrium of Caffeine and Theophylline on C18 Column Using Ionic Liquids as Additives - Bi, W.; Choi, D.K.; Row, K.H. (Asian Journal of Chemistry, 2010)
Comparison of caffeine and theophylline adsorption isotherm on C18 column using ionic liquids as mobile phase additives and the competitive adsorption of the two compounds were investigated. The experimental parameters of the equilibrium isotherms were determined via Langmuir isotherm model. The effects of the concentrations and the alkyl chain length of imidazolium ionic liquids on C18 particles were investigated.